Efektivitas Rational Emotive Behavioral Training terhadap Penurunan Kecemasan Menyusun Skripsi Mahasiswa - Kharisma A. Amaliyah; Sara Palila (Universitas Islam Indonesia, 2015)
This research aims to determine the effectiveness Training of Rational Emotive Behavioral to deriving arrange minithesis anxiety of college student in faculty of sciences and technology X University. The methode of group training REB require to deriving arrange minithesis anxiety. Sample in this research is college student in faculty of science and technology X University that arrange ministhesis. Total of subject in this research is sixteenth college student, that divide into two group 12 subject in control group and 4 subject in experimental group. This research is true experimental and the design used is pretest-posttest control group design. The methods of data analysis techniques which used is Mann Whitney U and Wilcoxon. The results of the data analysis between posttest control group and posttest experimental group showed a significance level of p = 0.274, it means there are not differences of arrange minithesis anxiety between control group and experimental group. The results of differences score pretest and posttest which used Wilcoxon showed a significance level of p = 0.068. It means there are not differences arrange minithesis anxiety between before and after training. So the conclusion is Training of Rational Emotive Behavioral not effective to deriving arrange minithesis anxiety. Keywords : REBT, arrange minithesis anxiety